STRUCTURING OPENINGS AND CLOSINGS IN THE LITERARY TEXT - Nurmetova Mohimjon Ortiq qizi (PEDAGOGS, 2024)
This study investigates the structural and thematic significance of openings and closings in literary texts, focusing on their role in narrative coherence, reader engagement, and thematic resonance. By analyzing 20 literary works from various genres and periods, the study identifies key strategies employed by authors to craft compelling openings and impactful closings. Findings suggest that openings introduce thematic frameworks and engage readers, while closings ensure resolution or provoke reflection. This research offers insights into how these elements enhance literary value and reader experience.